Firearm Dealers and Local Gun Violence: A Street Network Analysis of Shootings and Concentrated Disadvantage in Atlanta. (August 2022) - Semenza, Daniel C.; Griffiths, Elizabeth; Xu, Jie; Stansfield, Richard
Objectives: Examine the spatial relationship between firearm dealers and shootings in Atlanta. Methods: We combine data from the Atlanta Police Department (APD), the Bureau of Alcohol, Tobacco, Firearms, and Explosives (ATF), and the American Community Survey (ACS) to conduct a street network analysis from 2016 through 2018. We employ the Network Cross K Function to assess whether firearm dealers attract shootings in the city. We examine whether this spatial relationship differs by level of concentrated disadvantage in neighborhoods. Results: Without consideration of concentrated neighborhood disadvantage, firearm dealers and shootings are spatially unrelated to one another. Tract-level disadvantage influences the relationship between firearm dealers and shootings wherein dealers significantly attract shootings in disadvantaged neighborhoods. Conversely, shootings are located further from gun stores in non-disadvantaged communities. Shootings related to manslaughter and assault, but not robbery, are spatially associated with firearm dealers in disadvantaged neighborhoods. Conclusions: Building on prior research regarding firearm dealers and gun violence, we find support for an attraction effect in disadvantaged neighborhoods for certain types of shootings. We contextualize these findings within a broader discussion of how firearm dealers contribute to the complex ecology of local gun violence. This is important in light of federal policies and investments related to the prevention of and response to gun crime.